Experimental Demonstration of Nadir Echo Removal in SAR Using Waveform Diversity and Dual-Focus Postprocessing - Jeon, Se-Yeon; Kraus, Thomas; Steinbrecher, Ulrich; Krieger, Gerhard; Villano, Michelangelo (IEEE Geoscience and Remote Sensing Letters, 2022)
Synthetic aperture radar (SAR) provides high-resolution images for remote-sensing applications regardless of sunlight and weather conditions. The pulsed operation of SAR may lead to an occurrence of nadir echoes in SAR images that significantly affect the image quality in case the pulse repetition frequency (PRF), which is not properly constrained within the SAR system design. As an alternative, pulse-to-pulse variation of the transmitted waveform and dual-focus postprocessing can be exploited to remove the nadir echo and alleviate the PRF constraints (also in ScanSAR operation). This work provides a demonstration of the latter concept through an experimental acquisition of the TerraSAR-X satellite. The experiment is designed by selecting the scene and the acquisition parameters in order to have the nadir echo appearing in the SAR image. The waveform variation is achieved by alternating up- and down-chirps on transmit. The analysis of the results shows the effectiveness of dual-focus postprocessing for nadir echo suppression.
Created from Fastlane, Scopus look-up
Keywords: Dual-focus postprocessing; matched filtering; nadir echo; pulse repetition frequency (PRF); synthetic aperture radar (SAR); TerraSAR-X; up- and down-chirps; waveform diversity